Renal function in normal and disordered pregnancy - Hussein, Wael (2014)
PURPOSE OF REVIEW: Renal dysfunction during pregnancy is a common and serious complication. Understanding normal physiology during pregnancy provides a context to further describe changes in pregnancy that lead to renal dysfunction and may provide clues to better management. RECENT FINDINGS: Hormonal changes during pregnancy allow for increased blood flow to the kidneys and altered autoregulation such that glomerular filtration rate (GFR) increases significantly through reductions in net glomerular oncotic pressure and increased renal size. The mechanisms for maintenance of increased GFR change through the trimesters of pregnancy, continuing into the postpartum period. Important causes of pregnancy-specific renal dysfunction have been further studied, but much needs to be learned. Pre-eclampsia is due to abnormal placentation, with shifts in angiogenic proteins and the renin–angiotensin–aldosterone system leading to endothelial injury and clinical manifestations of hypertension and organ dysfunction. Other thrombotic microangiopathies occurring during pregnancy have been better defined as well, with new work focusing on the contribution of the complement system to these disorders. SUMMARY: Advances have been made in understanding the physiology of the kidney in normal pregnancy. Diseases that affect the kidney during pregnancy alter this physiology in various ways that inform clinicians on pathogenesis and may lead to improved therapeutic approaches and better outcomes of pregnancy.